Overview Of Life Safety Of Fishing Fishermen In Cilincing North Jakarta - Simson Katiandagho; Yuni Mariah; Nuradi; Entin Kartini (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
Working on a fishing vessel is work that is classified as dangerous and is prone to causing work accidents. The causes of accidents on fishing vessels are low crew awareness regarding work safety in shipping and fishing activities, low mastery of navigation and fishing safety competencies, ships are not equipped with safety equipment as they should be. Bad weather such as big waves and lack of knowledge and skills in using work safety equipment. Data collection was carried out by direct observation and interviews with fishermen in Ciincing. This research aims to find out the picture of the mental safety of Cilincing fishermen when going to sea. The results of this research show that the types of accidents frequently experienced by Cilincing fishermen are slips, bumps, falls into the sea, leaking boats, engine propellers caught in rubbish, sinking boats and ship collisions. The causes of work accidents experienced by Cilincing fishermen are a lack of skills in avoiding safety, incomplete safety equipment, inadequate vessels and a lack of navigational aids. The level of knowledge of Cilincing fishing fishermen about life safety is quite good because they often receive safety training and life safety equipment at sea. There are some fishermen who rely on traditional knowledge about sea safety based on experience passed down from their ancestors and combining knowledge. knowledge gained through government outreach.